Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/dom.14498
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing type 1 diabetes after multiple daily injections and capillary blood monitoring: Pump or sensor first? A meta‐analysis using pooled differences in outcome measures

Abstract: Aims: Most people living with type 1 diabetes self-manage using multiple daily injection (MDI) insulin regimens and self-monitoring of blood glucose (SMBG). Continuous subcutaneous insulin infusion (CSII) and continuous glucose monitoring (CGM) are adjuncts to education and support self-management optimization. The aim of this systematic review and meta-analysis was to assess which first-line technology is most effective. Methods: Electronic databases (MEDLINE, EMBASE and WEB OF SCIENCE) were systematically se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
(106 reference statements)
2
6
0
Order By: Relevance
“…CSII is also beneficial for all ages of those with T1D, as it is associated with lower HbA1c [ 14 , 20 , 28 , 33 , 48 52 ]. One pediatric study showed that when compared to MDI users, pump users had lower HbA1cs for 6 years of treatment follow-up [ 53 ].…”
Section: Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…CSII is also beneficial for all ages of those with T1D, as it is associated with lower HbA1c [ 14 , 20 , 28 , 33 , 48 52 ]. One pediatric study showed that when compared to MDI users, pump users had lower HbA1cs for 6 years of treatment follow-up [ 53 ].…”
Section: Devicesmentioning
confidence: 99%
“…In older adults with T1D, people using CSII were less likely to exhibit cognitive dysfunction compared to those using MDI [ 33 ]. Recent data from diabetes registries and cohort studies also demonstrate associations between insulin pump use and reduced rates of DKA [ 13 , 14 , 48 , 58 ], although two meta-analyses analyzing results of clinical trials found higher incidence of DKA in people using CSII when compared to MDI use [ 28 , 52 ]. Like CGMs, insulin pump use is supported by US and international T1D clinical treatment guidelines for both pediatric and adult populations.…”
Section: Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimated 63 % of adults with T1D in the US and 5-15 % of those in Europe use one [1,2]. The increasing uptake of insulin pump therapy (IPT) follows several meta-analyses of randomised controlled trials (RCTs) conducted in the past two decades of which most found a significant reduction in HbA 1c , compared with conventional treatment with multiple daily insulin injections (MDI) [3][4][5][6][7]. Although some RCTs have found reduced risk of diabetic ketoacidosis (DKA) and severe hypoglycaemia (SH), meta-analyses have found no or little effect on both outcomes or even an increased risk of DKA following IPT initiation [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…3 There are data suggesting that the addition of CGM to CSII further improves time in range and glucose variability. 4 However, it is notable that Ferm and colleagues 1 did not find that CGM use was associated with a reduced risk of DR. This lack of association may reflect CGM use in routine practice rather than its use in focused studies.…”
mentioning
confidence: 99%